Preliminary Observations on Viola calcarata as a Source of Bioactive Compounds: Antioxidant Activity and Phytochemical Profile of Two Alpine Subspecies - Nicole Mélanie Falla (MDPI AG, 2021)
Viola L. is a botanical genus with approximately 525 to 620 species, spread worldwide. Several violets are traditionally used as edible flowers and have been recently proved to be a source of bioactive compounds, including flavonols, flavanols, benzoic acids, and cinnamic acids. However, no information is available about the phytochemical profile of the Viola calcarata complex, which is found in the Alpine environment. Thus, the present research aimed to assess the antioxidant activity and the presence of bioactive compounds (anthocyanins and phenolic compounds) in V. calcarata subspecies, to promote their biodiversity and use in the agrifood sector. Two V. calcarata subspecies were chosen, with different colors: V. calcarata subspecies calcarata L., with white (CW), yellow (CY), and violet flowers (CV); and V. calcarata subspecies villarsiana (Roem & Schult.) Merxm., with bicolor (violet and yellow—VB) flowers. CY showed a significantly higher phenolic content (1116.43 mg GAE 100 g−1 FW) than the other subspecies, while CV showed higher values in anthocyanins content (44.73 mg C3G 100 g−1 FW). Regarding the antioxidant activity, CW (215.07 mmol Fe2+ kg−1 FW, 99.53 µmol TE g−1 FW, and 32.30 µmol TE g−1 FW for FRAP, DPPH, and ABTS, respectively) and VB (217.33 mmol Fe2+ kg−1 FW, 90.97 µmol TE g−1 FW, and 29.17 µmol TE g−1 FW for FRAP, DPPH, and ABTS, respectively) showed the highest values. Through HPLC, a total of eight phenolic compounds were quantitatively identified among the two subspecies, including flavonols, cinnamic acids, benzoic acids, catechins, and vitamin C. Though different in their composition, the two subspecies are rich in phenolic compounds, highlighting the importance of preserving their biodiversity and their potential use in the agrifood sector.